2020
DOI: 10.1007/s10668-020-00707-z
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian cuisine: comparison of environmental, economic and nutritional performance of two typical Brazilian dishes

Abstract: Brazilian cuisine is influenced by the diversity of geographical conditions, production of local ingredients and the multicultural character of foreign and native folks. In view of this context, we analyze sustainability issues in relation to the preparation of rice with jerky ("Arroz carreteiro"), and rice with chicken ("Galinhada"). This study is divided into two stages: environmental and economic analysis of food production process by life cycle analysis and nutritional assessment in comparison with the rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…During this period, it was also observed that most of the soybean cultivation area of Paraná (65.46%) had its maximum vegetative development in January and harvest in March (53.92%). The soybean culture contributes to the production chain and is dependent of the climatic events that can negatively affect the productivity and price of the product (da Costa et al, 2021). Variations in temperature and precipitation can lead to losses in soybean productivity Lu et al, 2021) Different dates for sowing in the spring-summer period (Johann et al, 2016;Yokoyama, et al, 2020) notwithstanding, it is possible to observe that sowing generally follows the ADAPAR ( 2017) recommendation, motivating the study of total rainfall in this period, considering the water requirements of the plant in the germination-emergence developmental phase (Rezende et al, 2003;Araya et al, 2015;Battisti & Sentelhas, 2015), and losses that may occur due to extreme events.…”
Section: Discussionmentioning
confidence: 99%
“…During this period, it was also observed that most of the soybean cultivation area of Paraná (65.46%) had its maximum vegetative development in January and harvest in March (53.92%). The soybean culture contributes to the production chain and is dependent of the climatic events that can negatively affect the productivity and price of the product (da Costa et al, 2021). Variations in temperature and precipitation can lead to losses in soybean productivity Lu et al, 2021) Different dates for sowing in the spring-summer period (Johann et al, 2016;Yokoyama, et al, 2020) notwithstanding, it is possible to observe that sowing generally follows the ADAPAR ( 2017) recommendation, motivating the study of total rainfall in this period, considering the water requirements of the plant in the germination-emergence developmental phase (Rezende et al, 2003;Araya et al, 2015;Battisti & Sentelhas, 2015), and losses that may occur due to extreme events.…”
Section: Discussionmentioning
confidence: 99%